DYNAMISM OF SUSTAINABLE URBAN DEVELOPMENT: ECONOMIC, SOCIAL, AND ENVIRONMENTAL INTEGRATION IN JAKARTA CITY PLANNING - Prayogi, Bagus (Universitas Malikussaleh, 2025)
The phenomenon of urbanization and rural-migration over the past few decades has become inevitable. Many factors affect the movement of the population, such as lack of job opportunities in the area of origin, income inequality, and uneven development. Urbanization and the resulting migrations demand adequate facilities for migrants. The dynamism of sustainable urban development requires economic, social and environmental integration to support and facilitate urbanites. Therefore, this study aims to identify the integration of urban development between economy, social and environment. The city that is the subject of the study is the city of Jakarta, which covers the period from 2015-2022. The data used is panel data by measuring urban development indicators against migration. So the analysis used is also panel data regression. In addition, urban metabolic analysis is also used to identify the most critical indicators of urban development and regions for migrants. Then the author will propose mitigation measures based on an alternative scenario approach.